2011
DOI: 10.1063/1.3558990
|View full text |Cite
|
Sign up to set email alerts
|

Carrier dynamics of InxGa1−xN quantum disks embedded in GaN nanocolumns

Abstract: Time-integrated and time-resolved microphotoluminescence studies have been performed on Inx Ga1−xN quantum disks at the tips of GaN nanocolumns. The results are analyzed in the context of current theories regarding an inhomogeneous strain distribution in the disk which is theorized to generate lateral charge separation in the disks by strain induced band bending, an inhomogeneous polarization field distribution, and Fermi surface pinning. It is concluded that no lateral separation of carriers occurs in the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…It has been shown that a radial strain gradient exists across the InGaN layer from its center to edge with its outer shell largely relaxed. 14,24 As such and noting that increasing the accelerating voltage of the electron beam increases its penetration depth into the nanorods, the changes in the observed CL with electron beam position and accelerating voltage should reflect the strain variation across the SQD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that a radial strain gradient exists across the InGaN layer from its center to edge with its outer shell largely relaxed. 14,24 As such and noting that increasing the accelerating voltage of the electron beam increases its penetration depth into the nanorods, the changes in the observed CL with electron beam position and accelerating voltage should reflect the strain variation across the SQD.…”
Section: Resultsmentioning
confidence: 99%
“…11 The formation of a nanorod structure, either by bottom-up epitaxial growth [2][3][4][5] or by dry etching a pre-existing epitaxial III-nitride layer, [6][7][8][9][10] has been proposed as a mean of alleviating strain due to the free surface presented by the sidewalls enabling the lattice to relax. [12][13][14] In the case of homogeneous nanorods formed by dry etching from c-plane homo-epitaxial GaN templates, the degree of strain relaxation in the overall structure will depend on the diameter and height of the nanorods, with complete strain relaxation occurring when their height exceeds their diameter irrespective of the type of substrate used. 15 When such etched nanorods contain an InGaN QW or a MQW oriented in the c-plane changes in the optical transition energy have been observed and are frequently ascribed to the impact of the strain relaxation in the nanorod on the piezoelectric contribution to the quantum-confined Stark effect (QCSE).…”
Section: Introductionmentioning
confidence: 99%
“…(2) and τ using Eq. (6). The understanding of the correlation is straightforward: In a QD with low E, the potential barrier height φ B is large.…”
Section: B Correlations Among Pl Propertiesmentioning
confidence: 99%
“…Note that we do not consider the contribution of the surface Fermi-level pinning [6,28], because it bends the conduction and valance bands in the same way and, hence, has negligible effects on the exciton potential profile.…”
Section: The Lateral Potential Barrier Profilementioning
confidence: 99%
“…Unfortunately, a large, strain-induced electric field in III-N heterostructures often severely suppresses the oscillator strength of the exciton and, hence, the radiative decay rate and the internal quantum efficiency (IQE). Since strain is relaxed near free surfaces, nanodisks (NDs) in nanowires, which has a large surfaceto-volume ratio, have been widely considered as a promising solution for improving the IQE of InGaN/GaN photonic devices [4][5][6][7][8][9][10][11] . The accompanying improvement in the radiative decay rate is also important for realizing ultrafast singlephoton sources using InGaN/GaN QDs 3,12 .…”
mentioning
confidence: 99%